To expand the expression \((4x - 3)(-3x^2 - 8x + 1)\) and write it in standard form, we will use the distributive property (also known as the FOIL method for binomials).
Step 1: Distribute \(4x\) to each term in the second polynomial:
\[ 4x \cdot (-3x^2) = -12x^3 \] \[ 4x \cdot (-8x) = -32x^2 \] \[ 4x \cdot (1) = 4x \]
Step 2: Distribute \(-3\) to each term in the second polynomial:
\[ -3 \cdot (-3x^2) = 9x^2 \] \[ -3 \cdot (-8x) = 24x \] \[ -3 \cdot (1) = -3 \]
Step 3: Combine all the results together:
Now we have:
\[ -12x^3 - 32x^2 + 4x + 9x^2 + 24x - 3 \]
Step 4: Combine like terms:
- For \(x^3\) terms: \(-12x^3\)
- For \(x^2\) terms: \(-32x^2 + 9x^2 = -23x^2\)
- For \(x\) terms: \(4x + 24x = 28x\)
- Constant term: \(-3\)
Final Result:
Putting it all together, we get:
\[ -12x^3 - 23x^2 + 28x - 3 \]
Thus, the expanded expression in standard form is:
\[ \boxed{-12x^3 - 23x^2 + 28x - 3} \]